Self-cleaning Ti-MoS2-Cu anti-microbial fouling titanium alloy and preparation method thereof

By preparing a gradient molybdenum titanium alloy matrix and performing copper ion release and vulcanization treatment, the problems of biofouling and poor self-cleaning ability of titanium alloy in complex environments are solved, and the self-cleaning and long-term antibacterial effects are achieved.

CN119710707AActive Publication Date: 2025-03-28XIAN UNIV OF TECH
View PDF 8 Cites 0 Cited by

Patent Information

Application Number
CN202411525077.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-03-28
Estimated Expiration
2044-10-30

AI Technical Summary

Technical Problem

Existing titanium alloy materials are prone to biofouling problems in complex and closed environments, and lack self-cleaning capabilities, which affects their use environment and maintenance costs.

Method used

By preparing a gradient molybdenum titanium alloy matrix, copper ions are released by arc discharge in a vacuum chamber, and then mixed with sulfur powder for vulcanization, forming a self-cleaning Ti-MoS2-Cu antimicrobial fouling titanium alloy.

Benefits of technology

It realizes the self-cleaning effect of titanium alloy, and has fast and long-term antibacterial ability, and can effectively kill bacteria and decompose dirty substances through photothermal and photocatalytic effects under the excitation of near-infrared light.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119710707A_ABST
    Figure CN119710707A_ABST
Patent Text Reader

Abstract

The invention discloses a self-cleaning Ti-MoS2-Cu anti-microbial fouling titanium alloy and a preparation method thereof. The preparation method specifically comprises the following steps: preparing a gradient molybdenum-titanium alloy matrix; the method comprises the following steps: pretreating a molybdenum-titanium alloy matrix with a chemical polishing solution, cleaning and drying, then connecting a negative electrode of a power supply, placing the molybdenum-titanium alloy matrix in a vacuum chamber containing a pure copper product, enabling pure copper to become copper plasma and release copper ions through arc discharge, then carrying out ion implantation, mixing an obtained Ti-Mo-Cu alloy precursor with sulfur powder, and carrying out sintering to obtain the titanium-molybdenum-Cu alloy. And carrying out vulcanization treatment in an atmosphere environment full of Ar, carrying out ultrasonic cleaning, and drying, so as to obtain the self-cleaning Ti-MoS2-Cu anti-microbial fouling titanium alloy. The Ti-MoS2-Cu titanium alloy capable of resisting microbial contamination and damage is mainly composed of copper ions with the antibacterial characteristic and a molybdenum-titanium alloy with a photo-thermal and photocatalytic nano molybdenum disulfide structure, so that the titanium alloy has the self-cleaning effect and can achieve rapid and long-acting bacteriostasis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of titanium alloy antibacterial material preparation, and specifically relates to a preparation method of a self-cleaning Ti-MoS2-Cu anti-microbial fouling titanium alloy, and also relates to the self-cleaning Ti-MoS2-Cu anti-microbial fouling titanium alloy. Background Art

[0002] Titanium alloys are widely used in daily life because of their light weight, high specific strength and corrosion resistance. For example, in the medical field, aerospace field, marine engineering, etc., titanium alloys are often made into implants, metal shells, hulls, oil pipelines, etc. However, titanium alloys themselves do not have antibacterial properties. In some complex and closed working environments, it is inevitable to encounter biological fouling problems, which in turn affects the original use environment and is not conducive to normal use and maintenance in the future. Titanium alloys with self-cleaning properties can keep their surfaces clean and remove pollutants, reduce maintenance costs and improve equipment reliability, ensuring the normal operation of equipment in extreme environments. Therefore, the study of self-cleaning and anti-microbial fouling titanium alloys has a wide range of needs and important significance.

[0003] A Chinese patent (application number: 202311490724.4, publication number: CN 117548676 A, publication date: 2024-02-13) discloses a method for preparing a low-cost, high-efficiency antibacterial copper-titanium alloy sheet, by mixing titanium powder and copper powder, and then obtaining a copper-titanium alloy with antibacterial effect by sealing, die-casting, hot pressing sintering, cold rolling, etc. Although the copper-titanium alloy can achieve the effect of anti-biological fouling by releasing copper ions, it cannot achieve self-cleaning and thus affect subsequent use. A Chinese patent (application number: 202210944819.8, publication number: CN 117568785A, publication date: 2024-02-20) discloses a method for preparing a coating, using an atomic layer deposition method to first prepare an aluminum oxide transition layer on a titanium alloy substrate, and then using an atomic layer deposition method to deposit a zinc oxide antibacterial material, and growing a layer of molecular sieve film with antibacterial effect on the surface of pure titanium or titanium alloy. However, although the antibacterial coating made by atomic deposition can achieve resistance to biofouling, it cannot achieve self-cleaning, and the anti-fouling effect is slow. A Chinese patent (application number: 202310052559.8, publication number: CN 116115836A, publication date: 2023-05-16) discloses a surface coating, preparation method and application for improving the antibacterial properties of the surface of pure titanium or titanium alloy, and the antibacterial effect is achieved by preparing a coating composed of an inner layer, an intermediate transition layer and an outer layer on the surface of titanium and titanium alloys and containing nano-Ag. However, by releasing ions to resist biofouling, the self-cleaning effect of titanium alloy cannot be achieved for reuse. Summary of the invention

[0004] The purpose of the present invention is to provide a preparation method of a self-cleaning Ti-MoS2-Cu anti-microbial fouling titanium alloy, which solves the problem that the existing titanium alloy materials have poor anti-fouling and self-cleaning capabilities.

[0005] Another object of the present invention is to provide a self-cleaning Ti-MoS2-Cu titanium alloy that is resistant to microbial fouling.

[0006] The technical solution adopted by the present invention is a method for preparing a self-cleaning Ti-MoS2-Cu anti-microbial contamination titanium alloy, which is specifically implemented according to the following steps: Step 1, preparing a gradient molybdenum-titanium alloy substrate; Step 2, pre-treating the molybdenum-titanium alloy substrate in step 1 with a chemical polishing solution, cleaning and drying, then connecting the negative electrode of the power supply and placing it in a vacuum chamber containing a pure copper product, using arc discharge to convert the pure copper into copper plasma and release copper ions, followed by ion implantation to obtain a Ti-Mo-Cu alloy precursor; Step 3, mixing the Ti-Mo-Cu alloy precursor obtained in step 2 with sulfur powder, performing a sulfurization treatment in an Ar atmosphere, ultrasonically cleaning, and drying to obtain a self-cleaning Ti-MoS2-Cu anti-microbial contamination titanium alloy.

[0007] The present invention is also characterized in that: In step 1, specifically: Step 1.1, mixing titanium powder and molybdenum powder with anhydrous ethanol respectively, ball milling with a ball mill, and drying to obtain molybdenum-titanium mixed powder; Step 1.2, first lay a layer of pure titanium powder and then stack five layers of molybdenum-titanium mixed powder, and gradually increase the molybdenum content in the molybdenum-titanium mixed powder. After laying fully, use a die-casting machine to perform static die-casting, then hot-press sintering in an atmosphere containing Ar, and annealing and cooling to obtain a molybdenum-titanium alloy matrix.

[0008] In step 1.1, the ball-to-material ratio during ball milling is 4:1; the rotation speed is 100-200 rpm; the ball milling time is 20-24 h; and the particle sizes of molybdenum powder and titanium powder are both 100 nm-1 μm.

[0009] In step 1.2, the content of the first layer of pure titanium powder accounts for 10% of the total mass of the molybdenum-titanium alloy matrix; the content of the first layer of molybdenum-titanium mixed powder accounts for 12% of the total mass of the molybdenum-titanium alloy matrix; in the first layer of molybdenum-titanium mixed powder, the mass ratio of molybdenum powder to titanium powder is 1:9; the content of the second layer of molybdenum-titanium mixed powder accounts for 15% of the total mass of the molybdenum-titanium alloy matrix; in the second layer of molybdenum-titanium mixed powder, the mass ratio of molybdenum powder to titanium powder is 1.5:8.5; the content of the third layer of molybdenum-titanium mixed powder accounts for 18% of the total mass of the molybdenum-titanium alloy matrix; in the third layer of molybdenum-titanium mixed powder, the mass ratio of molybdenum powder to titanium powder is 2:8; the content of the fourth layer of molybdenum-titanium mixed powder accounts for 21% of the total mass of the molybdenum-titanium alloy matrix; in the fourth layer of molybdenum-titanium mixed powder, the mass ratio of molybdenum powder to titanium powder is 2.5:7.5; the content of the fifth layer of molybdenum-titanium mixed powder accounts for 24% of the total mass of the molybdenum-titanium alloy matrix; in the fifth layer of molybdenum-titanium mixed powder, the mass ratio of molybdenum powder to titanium powder is 3:7.

[0010] In step 1.2, the static pressing pressure is 180~200MPa; the holding time is 5~10min; the sintering temperature is 1800~2000℃; the sintering pressure is 20~40MPa; the sintering time is 140~180min; and the annealing temperature is 1550℃.

[0011] In step 2, the chemical polishing liquid is composed of nitric acid, hydrofluoric acid and deionized water in a volume ratio of 4:1:10; during ion injection, the pulse voltage frequency is 10-12 Hz; the duration of the pulse voltage is 5 s; the pulse voltage is 30-40 kV; the air pressure of the vacuum chamber is 5 10 -3 Pa; the ion injection time is 1~3h.

[0012] In step 3, the mass ratio of sulfur powder to molybdenum powder in molybdenum-titanium alloy is 2:1; the vulcanization temperature is 900-1200° C.; and the vulcanization time is 10-12 hours.

[0013] Another technical solution adopted by the present invention is a self-cleaning Ti—MoS2—Cu anti-microbial fouling titanium alloy prepared by a preparation method of the self-cleaning Ti—MoS2—Cu anti-microbial fouling titanium alloy.

[0014] The beneficial effects of the present invention are: (1) The Ti-MoS2-Cu anti-microbial fouling titanium alloy of the present invention is mainly composed of copper ions with antibacterial properties and a molybdenum-titanium alloy with a photothermal and photocatalytic nano-molybdenum disulfide structure, which enables it to have a self-cleaning effect and can quickly and long-term inhibit bacteria. In addition, the internal MoS2 can use photothermal effects under the excitation of near-infrared light and cooperate with the release of copper ions injected into the alloy to quickly kill bacteria on the surface of the alloy to achieve the effect of anti-biological fouling; (2) The Ti-MoS2-Cu anti-microbial fouling titanium alloy of the present invention can utilize photocatalysis to decompose dead bacteria adhering to the surface of the alloy under the excitation of near-infrared light, thereby achieving a self-cleaning effect. BRIEF DESCRIPTION OF THE DRAWINGS FIG. 1 is a schematic diagram of the internal structure of the self-cleaning Ti-MoS2-Cu anti-microbial fouling titanium alloy of the present invention. DETAILED DESCRIPTION

[0015] The present invention is described in detail below with reference to the accompanying drawings and specific embodiments.

[0016] The preparation method of the self-cleaning Ti-MoS2-Cu anti-microbial fouling titanium alloy of the present invention is specifically implemented according to the following steps: Step 1, preparing a gradient molybdenum-titanium alloy substrate, specifically: Step 1.1, mixing high-purity titanium powder and molybdenum powder with anhydrous ethanol respectively, milling with a ball mill, and drying to obtain molybdenum-titanium mixed powder; The ball-to-material ratio during ball milling is 4:1; the rotation speed is 100-200 rpm; the ball milling time is 20-24 hours; The particle sizes of molybdenum powder and titanium powder are both 100nm~1μm; Step 1.2, first lay a layer of pure titanium powder and then stack five layers of molybdenum-titanium mixed powder, and gradually increase the molybdenum content in the molybdenum-titanium mixed powder. After the powder is fully laid, a die-casting machine is used to perform static die-casting, and then hot-pressing sintering is performed in an atmosphere containing Ar, and then annealing and cooling are performed to obtain a molybdenum-titanium alloy matrix; The content of the first layer of pure titanium powder accounts for 10% of the total mass of the molybdenum-titanium alloy matrix; The content of the first layer of molybdenum-titanium mixed powder accounts for 12% of the total mass of the molybdenum-titanium alloy matrix; in the first layer of molybdenum-titanium mixed powder, the mass ratio of molybdenum powder to titanium powder is 1:9; The content of the second layer of molybdenum-titanium mixed powder accounts for 15% of the total mass of the molybdenum-titanium alloy matrix; in the second layer of molybdenum-titanium mixed powder, the mass ratio of molybdenum powder to titanium powder is 1.5:8.5; The content of the third layer of molybdenum-titanium mixed powder accounts for 18% of the total mass of the molybdenum-titanium alloy matrix; in the third layer of molybdenum-titanium mixed powder, the mass ratio of molybdenum powder to titanium powder is 2:8; The content of the fourth layer of molybdenum-titanium mixed powder accounts for 21% of the total mass of the molybdenum-titanium alloy matrix; in the fourth layer of molybdenum-titanium mixed powder, the mass ratio of molybdenum powder to titanium powder is 2.5:7.5; The content of the fifth layer of molybdenum-titanium mixed powder accounts for 24% of the total mass of the molybdenum-titanium alloy matrix; in the fifth layer of molybdenum-titanium mixed powder, the mass ratio of molybdenum powder to titanium powder is 3:7; Static pressing pressure is 180~200MPa; holding time is 5~10min; The sintering temperature is 1800~2000℃; the sintering pressure is 20~40MPa; the sintering time is 140~180min; and the annealing temperature is 1550℃.

[0017] Step 2, preparing a copper ion-doped Ti-Mo-Cu alloy precursor, specifically: The molybdenum-titanium alloy substrate in step 1 is pretreated with a chemical polishing liquid, cleaned and dried, then connected to the negative electrode of a power supply and placed in a vacuum chamber containing a pure copper product, and the pure copper is converted into copper plasma and copper ions are released by arc discharge, followed by ion implantation to obtain a Ti-Mo-Cu alloy precursor; The chemical polishing solution is composed of nitric acid, hydrofluoric acid and deionized water in a volume ratio of 4:1:10; During ion implantation, the pulse voltage frequency is 10~12Hz; the pulse voltage duration is 5s; the pulse voltage is 30~40kV; the pressure of the vacuum chamber is 5 10 -3 Pa; the ion injection time is 1~3h; Step 3, preparing a self-cleaning Ti-MoS2-Cu anti-microbial fouling titanium alloy, specifically: The copper ion-doped Ti-Mo-Cu alloy precursor obtained in step 2 is mixed with sulfur powder, The self-cleaning Ti-MoS2-Cu titanium alloy resistant to microbial contamination is obtained by sulfurizing, ultrasonic cleaning and drying in an Ar atmosphere. The mass ratio of sulfur powder to molybdenum powder in molybdenum-titanium alloy is 2:1; the vulcanization temperature is 900-1200°C; the vulcanization time is 10-12h; Figure 1 This is a schematic diagram of the internal structure of the self-cleaning Ti-MoS2-Cu antimicrobial fouling titanium alloy of the present invention. It is a reusable anti-fouling titanium alloy prepared by powder metallurgy, ion implantation and combined with sulfurization reaction. It is mainly composed of copper ions with antibacterial properties and a molybdenum-titanium alloy with a nano-molybdenum disulfide structure having photothermal and photocatalytic properties. The molybdenum-titanium alloy matrix is ​​synthesized by mixing molybdenum powder and titanium powder through powder metallurgy; copper ions can be doped into the molybdenum-titanium alloy through ion implantation. The molybdenum disulfide structure can be converted into a molybdenum disulfide structure inside the molybdenum-titanium alloy through the sulfurization process, and finally a titanium alloy with a Ti-MoS2-Cu structure is obtained, which has a self-cleaning effect and can quickly and long-lastingly inhibit bacteria.

[0018] Example 1 After mixing high-purity titanium powder and molybdenum powder with a particle size of 100nm with anhydrous ethanol, zirconium oxide balls were added at a ball-to-material ratio of 4:1, and the sample was milled for 20 hours at a speed of 100rpm; after drying the sample, a layer of pure titanium powder was first laid, and then five layers of molybdenum-titanium mixed powder were superimposed, and the molybdenum content in the molybdenum-titanium mixed powder was increased layer by layer. After laying, a die-casting machine was used at a pressure of 180MPa for 5 minutes. After casting, it was hot-pressed and sintered at 1800℃ for 140min in an atmosphere containing Ar at a pressure of 20MPa, and then annealed and cooled at 1550℃ to obtain a molybdenum-titanium alloy matrix.

[0019] The content of the first layer of pure titanium powder accounts for 10% of the total mass of the molybdenum-titanium alloy matrix; The content of the first layer of molybdenum-titanium mixed powder accounts for 12% of the total mass of the molybdenum-titanium alloy matrix; in the first layer of molybdenum-titanium mixed powder, the mass ratio of molybdenum powder to titanium powder is 1:9; The content of the second layer of molybdenum-titanium mixed powder accounts for 15% of the total mass of the molybdenum-titanium alloy matrix; in the second layer of molybdenum-titanium mixed powder, the mass ratio of molybdenum powder to titanium powder is 1.5:8.5; The content of the third layer of molybdenum-titanium mixed powder accounts for 18% of the total mass of the molybdenum-titanium alloy matrix; in the third layer of molybdenum-titanium mixed powder, the mass ratio of molybdenum powder to titanium powder is 2:8; The content of the fourth layer of molybdenum-titanium mixed powder accounts for 21% of the total mass of the molybdenum-titanium alloy matrix; in the fourth layer of molybdenum-titanium mixed powder, the mass ratio of molybdenum powder to titanium powder is 2.5:7.5; The content of the fifth layer of molybdenum-titanium mixed powder accounts for 24% of the total mass of the molybdenum-titanium alloy matrix; in the fifth layer of molybdenum-titanium mixed powder, the mass ratio of molybdenum powder to titanium powder is 3:7; The obtained molybdenum-titanium alloy substrate was pretreated with a chemical polishing solution consisting of nitric acid, hydrofluoric acid and deionized water in a volume ratio of 4:1:10. After cleaning and drying, it was connected to the negative electrode of a high-voltage power supply and placed on a sample holder. It was then immersed in a gas pressure of 5 10 -3 Pa is placed in a vacuum chamber of positively charged copper plasma. The parameters of pulse voltage frequency of 10 Hz, pulse voltage duration of 5 s, and pulse voltage of 30 kV are continuously injected for 1 hour to obtain a Ti-Mo-Cu alloy precursor doped with copper ions.

[0020] A certain mass of sulfur powder is weighed so that the mass ratio of sulfur powder to molybdenum powder in the molybdenum-titanium alloy is 2: 1. The prepared precursor sample is then placed in an Ar atmosphere with sulfur powder, sulfurized at 900°C for 10 hours, and then ultrasonically cleaned (ultrasonic cleaning with water) and dried to obtain a self-cleaning Ti-MoS2-Cu anti-microbial contamination titanium alloy.

[0021] Example 2 High-purity titanium powder and molybdenum powder with a particle size of 100nm were mixed with anhydrous ethanol respectively, and zirconium oxide balls were added at a ball-to-material ratio of 4:1. The ball mill was used for ball milling at a speed of 150rpm for 20h. After the ground sample was dried, a layer of pure titanium powder was first laid and then five layers of molybdenum-titanium mixed powder were stacked, and the molybdenum content in the molybdenum-titanium mixed powder was increased layer by layer. After the sample was fully laid, a die-casting machine was used to maintain the pressure for 5 minutes at a pressure of 190MPa. After casting, it was hot-pressed and sintered at 1900℃ for 140min in an atmosphere containing Ar at a pressure of 30MPa, and then annealed and cooled at 1550℃ to obtain a molybdenum-titanium alloy matrix. The obtained molybdenum-titanium alloy matrix was pretreated with a chemical polishing solution composed of nitric acid, hydrofluoric acid and deionized water in a volume ratio of 4:1:10. After cleaning and drying, it was connected to the negative electrode of the high-voltage power supply and placed on the sample holder, and then immersed in a pressure of 5 10 -3 Pa is placed in a vacuum chamber in a copper plasma with positive charge. The Ti-Mo-Cu alloy precursor doped with copper ions is prepared by continuous injection for 3 hours with the parameters of pulse voltage frequency of 12Hz; pulse voltage duration of 5s; pulse voltage of 35kV. A certain mass of sulfur powder is weighed so that the mass ratio of sulfur powder to molybdenum powder in molybdenum-titanium alloy is 2:1. The prepared precursor sample is then placed in an environment with sulfur powder and filled with Ar atmosphere, sulfurized at 1050℃ for 12h, then ultrasonically cleaned and dried to obtain a self-cleaning Ti-MoS2-Cu anti-microbial contamination titanium alloy.

[0022] Example 3 High-purity titanium powder and molybdenum powder with a ratio of molybdenum atoms to titanium atoms of 2:8 and a particle size of 1μm were mixed with anhydrous ethanol respectively, and zirconium oxide balls were added at a ball-to-material ratio of 4:1. The ball mill was used for 24 hours at a speed of 200rpm. After the ground sample was dried, a layer of pure titanium powder was first laid and then five layers of molybdenum-titanium mixed powder were superimposed, and the molybdenum content in the molybdenum-titanium mixed powder was increased layer by layer. After the sample was fully laid, a die-casting machine was used to maintain the pressure for 10 minutes at a pressure of 200MPa. After casting, it was hot-pressed and sintered at 2000℃ for 180min in an atmosphere containing Ar at a pressure of 40MPa, and then annealed and cooled at 1550℃ to obtain a molybdenum-titanium alloy matrix. The obtained molybdenum-titanium alloy matrix was pretreated with a chemical polishing solution composed of nitric acid, hydrofluoric acid and deionized water in a volume ratio of 4:1:10. After cleaning and drying, it was connected to the negative electrode of the high-voltage power supply and placed on the sample holder, and then immersed in a pressure of 5 10 -3Pa is placed in a vacuum chamber in a positively charged copper plasma. The parameters of pulse voltage frequency of 12Hz; pulse voltage duration of 5s; pulse voltage of 40kV are continuously injected for 3h to obtain a Ti-Mo-Cu alloy precursor doped with copper ions. A certain mass of sulfur powder is weighed so that the mass ratio of sulfur powder to molybdenum powder in the molybdenum-titanium alloy is 2:1. The prepared precursor sample is then placed in an environment containing sulfur powder and filled with Ar atmosphere, sulfurized at 1100℃ for 12h, and then ultrasonically cleaned and dried to obtain a self-cleaning Ti-MoS2-Cu anti-microbial contamination titanium alloy. Example 4 High-purity titanium powder and molybdenum powder with a particle size of 1 μm and a ratio of molybdenum atoms to titanium atoms of 2:8 were mixed with anhydrous ethanol respectively, and zirconium oxide balls were added at a ball-to-material ratio of 4:1. The ball mill was used for 20 hours at a speed of 200 rpm. After the ground sample was dried, a layer of pure titanium powder was first laid and then five layers of molybdenum-titanium mixed powder were stacked, and the molybdenum content in the molybdenum-titanium mixed powder was increased layer by layer. After the sample was fully laid, a die-casting machine was used to maintain the pressure for 5 minutes at a pressure of 200 MPa. After casting, it was hot-pressed and sintered at 2000°C for 140 minutes in an atmosphere containing Ar at a pressure of 40 MPa, and then annealed and cooled at 1550°C to obtain a molybdenum-titanium alloy matrix. The obtained molybdenum-titanium alloy matrix was pretreated with a chemical polishing solution composed of nitric acid, hydrofluoric acid and deionized water in a volume ratio of 4:1:10. After cleaning and drying, it was connected to the negative electrode of the high-voltage power supply and placed on the sample holder, and then immersed in a pressure of 5 10 -3 Pa is placed in a vacuum chamber in a positively charged copper plasma. The parameters of pulse voltage frequency of 12Hz; pulse voltage duration of 5s; pulse voltage of 40kV are continuously injected for 1h to obtain a Ti-Mo-Cu alloy precursor doped with copper ions. A certain mass of sulfur powder is weighed so that the mass ratio of sulfur powder to molybdenum powder in the molybdenum-titanium alloy is 2:1. The prepared precursor sample is then placed in an environment containing sulfur powder and filled with Ar atmosphere, and sulfurized at 1100℃ for 10h. After ultrasonic cleaning and drying, a self-cleaning Ti-MoS2-Cu anti-microbial fouling titanium alloy can be obtained. The self-cleaning Ti-MoS2-Cu antimicrobial fouling titanium alloy prepared in Examples 1-4 of the present invention can be antibacterial through the release of copper ions and the synergistic effect of light and heat. Examples 1-4, TC4, and copper-titanium alloy were irradiated under near-infrared light for 10 minutes, and the temperature rise results are shown in Table 1.

[0023] Table 1 Temperature rise results of Examples 1-4 and the control group under near-infrared light irradiation

[0024] To study its antibacterial properties, the control group was TC4 and copper-titanium alloy, which were co-cultured with Escherichia coli and Staphylococcus aureus for 24 hours under dark conditions and under near-infrared light irradiation. The antibacterial results are shown in Table 2 and Table 3. It can be seen from Table 2 and Table 3 that the antibacterial rate of the self-cleaning Ti-MoS2-Cu titanium alloy is above 90% regardless of whether it is in the dark or under light conditions. After applying light, its antibacterial rate is above 97%. In comparison, a self-cleaning Ti-MoS2-Cu anti-microbial contamination titanium alloy prepared by the present invention has a better antibacterial effect.

[0025] Table 2 Antibacterial rate of co-culture of Examples 1-4 and the control group in dark environment

[0026] Table 3 Antibacterial rate of co-culture of Examples 1-4 and the control group under light environment

[0027] The self-cleaning Ti-MoS2-Cu anti-microbial fouling titanium alloy of the present invention achieves antibacterial and self-cleaning effects through photocatalysis. For this reason, Examples 1-4 and the control group were co-cultured with Escherichia coli for 7 consecutive days under light conditions. After each first day of co-culture, the sample was taken out, irradiated with infrared light for 30 minutes, and then continued to co-cultivate on the second day, and this operation was repeated until the 7th day. The antibacterial rate results are shown in Table 4. It can be seen that during the 7 days of co-cultivation, the antibacterial rate of Examples 1-4 was stably maintained at more than 97%. This better illustrates that the self-cleaning Ti-MoS2-Cu anti-microbial fouling titanium alloy prepared by the present invention has excellent anti-fouling ability and also has excellent self-cleaning effect.

[0028] Table 4 Antibacterial rate of Example 1-4 and the control group co-cultured for 7 days under light environment

Claims

1. A method for preparing a self-cleaning Ti-MoS2-Cu titanium alloy that resists microbial contamination, characterized in that: Follow the steps below to implement it: Step 1, preparing a gradient molybdenum-titanium alloy substrate; Step 2, pre-treating the molybdenum-titanium alloy substrate in step 1 with a chemical polishing solution, cleaning and drying, then connecting the negative electrode of the power supply and placing it in a vacuum chamber containing a pure copper product, using arc discharge to convert the pure copper into copper plasma and release copper ions, followed by ion implantation to obtain a Ti-Mo-Cu alloy precursor; Step 3, mixing the Ti-Mo-Cu alloy precursor obtained in step 2 with sulfur powder, performing a sulfurization treatment in an Ar atmosphere, ultrasonically cleaning, and drying to obtain a self-cleaning Ti-MoS2-Cu anti-microbial contamination titanium alloy.

2. The method for preparing the self-cleaning Ti-MoS2-Cu anti-microbial fouling titanium alloy according to claim 1, characterized in that: In the step 1, specifically: Step 1.1, mixing titanium powder and molybdenum powder with anhydrous ethanol respectively, ball milling with a ball mill, and drying to obtain molybdenum-titanium mixed powder; Step 1.2, first lay a layer of pure titanium powder and then stack five layers of molybdenum-titanium mixed powder, and gradually increase the molybdenum content in the molybdenum-titanium mixed powder. After laying fully, use a die-casting machine to perform static die-casting, then hot-press sintering in an atmosphere containing Ar, and annealing and cooling to obtain a molybdenum-titanium alloy matrix.

3. The method for preparing the self-cleaning Ti-MoS2-Cu anti-microbial fouling titanium alloy according to claim 2, characterized in that: In the step 1.1, the ball-to-material ratio during ball milling is 4:1; the rotation speed is 100-200 rpm; the ball milling time is 20-24 h; and the particle sizes of the molybdenum powder and the titanium powder are both 100 nm-1 μm.

4. The method for preparing the self-cleaning Ti-MoS2-Cu anti-microbial fouling titanium alloy according to claim 2, characterized in that: In the step 1.2, the content of the first layer of pure titanium powder accounts for 10% of the total mass of the molybdenum-titanium alloy matrix; the content of the first layer of molybdenum-titanium mixed powder accounts for 12% of the total mass of the molybdenum-titanium alloy matrix; in the first layer of molybdenum-titanium mixed powder, the mass ratio of molybdenum powder to titanium powder is 1:9; the content of the second layer of molybdenum-titanium mixed powder accounts for 15% of the total mass of the molybdenum-titanium alloy matrix; in the second layer of molybdenum-titanium mixed powder, the mass ratio of molybdenum powder to titanium powder is 1.5:8.5; the content of the third layer of molybdenum-titanium mixed powder accounts for 18% of the total mass of the molybdenum-titanium alloy matrix; in the third layer of molybdenum-titanium mixed powder, the mass ratio of molybdenum powder to titanium powder is 2:8; the content of the fourth layer of molybdenum-titanium mixed powder accounts for 21% of the total mass of the molybdenum-titanium alloy matrix; in the fourth layer of molybdenum-titanium mixed powder, the mass ratio of molybdenum powder to titanium powder is 2.5:7.5; the content of the fifth layer of molybdenum-titanium mixed powder accounts for 24% of the total mass of the molybdenum-titanium alloy matrix; in the fifth layer of molybdenum-titanium mixed powder, the mass ratio of molybdenum powder to titanium powder is 3:

7.

5. The method for preparing the self-cleaning Ti-MoS2-Cu anti-microbial fouling titanium alloy according to claim 2, characterized in that: In the step 1.2, the static pressing pressure is 180-200 MPa; the holding time is 5-10 min; the sintering temperature is 1800-2000° C.; the sintering pressure is 20-40 MPa; the sintering time is 140-180 min; and the annealing temperature is 1550° C.

6. The method for preparing the self-cleaning Ti-MoS2-Cu anti-microbial fouling titanium alloy according to claim 1, characterized in that: In step 2, the chemical polishing liquid is composed of nitric acid, hydrofluoric acid and deionized water in a volume ratio of 4:1:10; during ion injection, the pulse voltage frequency is 10-12 Hz; the duration of the pulse voltage is 5 s; the pulse voltage is 30-40 kV; the air pressure of the vacuum chamber is 5 10 -3 Pa; the ion injection time is 1~3h.

7. The method for preparing the self-cleaning Ti-MoS2-Cu anti-microbial fouling titanium alloy according to claim 1, characterized in that: In the step 3, the vulcanization temperature is 900-1200° C. and the vulcanization time is 10-12 hours.

8. The self-cleaning Ti—MoS2—Cu anti-microbial fouling titanium alloy prepared by the method for preparing the self-cleaning Ti—MoS2—Cu anti-microbial fouling titanium alloy according to any one of claims 1 to 7.

Citation Information

Patent Citations

  • Preparation method of copper cemented layer on titanium alloy surface

    CN102676985A

  • Medical ti-based composite coating with bone repair function and antibacterial performance and preparing method of coating

    CN107304472A

  • Preparation method and application of photocatalytic material of molybdenum and sulfur doped titanium dioxide

    CN109364955A

  • Space mechanism high-binding-force solid antibacterial lubricating film layer and preparation method thereof

    CN109576641A

  • Molybdenum disulfide sulfide / copper composite film and preparation method and application thereof

    CN114574826A